Markers of cellular senescence is associated with persistent pulmonary pathology after COVID-19 infection. Issue 12 (2nd December 2022) - Lekva, Tove; Ueland, Thor; Halvorsen, Bente; Murphy, Sarah Louise; Dyrhol-Riise, Anne Ma; Tveita, Anders; Finbråten, Ane-Kristine; Mathiessen, Alexander; Müller, Karl Erik; Aaløkken, Trond Mogens; Skjønsberg, Ole Henning; Lerum, Tøri Vigeland; et al.
Abstract: Background: The lungs are the organ most likely to sustain serious injury from coronavirus disease 2019 (COVID-19). However, the mechanisms for long-term complications are not clear. Patients with severe COVID-19 have shorter telomere lengths and higher levels of cellular senescence, and we hypothesized that circulating levels of the telomere-associated senescence markers chitotriosidase, β-galactosidase, cathelicidin antimicrobial peptide and stathmin 1 (STMN1) were elevated in hospitalized COVID-19 patients compared to controls and could be associated with pulmonary sequelae following hospitalization. Methods: Ninety-seven hospitalized patients with COVID-19 who underwent assessment for pulmonary sequelae at three-month follow-up were included in the study. β-Galactosidase and chitotriosidase were analysed by fluorescence; stathmin 1 and cathelicidin antimicrobial peptide were analysed by enzyme immuno-assay in plasma samples from the acute phase and after three-months. In addition, the classical senescence markers cyclin-dependent kinase inhibitor 1A and 2A were analysed by enzyme immuno-assay in peripheral blood mononuclear cell lysate after three months. Results: We found elevated plasma levels of the senescence markers chitotriosidase and stathmin 1 in patients three months after hospitalization with COVID-19, and these markers in addition to protein levels of cyclin-dependent kinase inhibitor 2A in cell lysate, were associated with pulmonary pathology. The elevated levels of these markers seem to reflect both age-dependent (chitotriosidase) and age-independent (stathmin 1, cyclin-dependent kinase inhibitor 2A) processes. Conclusions: We suggest that accelerated ageing or senescence could be important for long-term pulmonary complications of COVID-19, and our findings may be relevant for future research exploring the pathophysiology and management of these patients.